Role of Ukraine in realization international economic-legal mechanisms maintenance of ecological safety - Боярська, Зоя Іванівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In article it is analised forms of participation of Ukraine in performance of the international mechanisms of maintenance of global ecological safety.